APLIKASI PEMBELAJARAN DISIPLIN DALAM PIPS DI SMK NEGERI 3 MARABAHAN KABUPATEN BARITO KUALA - Dese Yoelani Wikaryo (JURNAL SOCIUS, 2016)
This research found that: (1) description of learning process in SMK Negeri is generally good and using KTSP curriculum. (2) Application of Discipline Learning in Social Study Program in SMK Negeri 3 Marabahan such as discipline in entering the classroom on time after break, neatness of dress discipline, using the completeness or attributes of uniform,  doing homework assignment discipline, discipline of argues, going to school discipline, and so on. application of discipline learning in SMK Negeri 3 is social studies teacher tries to apply implementation of discipline through application of discipline learning with educational sanction such as learning while standing upright in front of the bench for those who does violations such as can not giving opinion, not doing the homework or task, not bringing notebook and LKS book, being late to class, students are not wearing a tie, belt, or other school supplies. (3) implication of application of discipline learning in social study program is that students not to repeat the offense so that indirectly by the application of discipline learning the discipline of students gradually begin to decrease violations.Kata Kunci: pembelajaran disiplin IPS,aplikasi, implikasi